2014
DOI: 10.1097/hjh.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Is there a differential impact of parity on blood pressure by age?

Abstract: Our analyses yield differential effects of parity on BP in older vs. younger women. Reductions in BP in younger parous women have been described before; the opposite impact in older women is new. The findings may constitute biological mechanisms in an aging population or reflect birth cohort effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
11
1
2
Order By: Relevance
“…16 A separate prior investigation demonstrated that this inverse association may only be present in younger versus older cohorts of women. 17 We extended prior findings by accounting for several pregnancy complications, including preeclampsia.…”
Section: Discussionmentioning
confidence: 78%
“…16 A separate prior investigation demonstrated that this inverse association may only be present in younger versus older cohorts of women. 17 We extended prior findings by accounting for several pregnancy complications, including preeclampsia.…”
Section: Discussionmentioning
confidence: 78%
“…As maternal protection conferred by delivery, an inverse correlation between parity and the prevalence of hypertension has been previously reported. 14 15) According to similar series studies performed on this topic, as parity increased, the blood pressure decreased up to 20 years after delivery. 9) In addition, improved functions of vascular endothelial cells were maintained even after delivery, according to some reports.…”
Section: Discussionmentioning
confidence: 95%
“… 19 20 21) The inconsistency among the previous observations might arise from the study design, number of enrolled patients, and adjustment for confounding variables. 15) In particular, according to many studies, the key risk factors for hypertension in women, such as age, menopause, and BMI, serve as the greatest confounding variables. 15) …”
Section: Discussionmentioning
confidence: 99%
“…30 A change in paternity is probably the best known risk factor for PE in multiparous women, with OR of 1.30-1.56 for PE, depending on the diagnostic criteria, and an OR of 1.99 for the combined group of pregnancy-related hypertensive disorders regardless of diagnostic criteria. In general, multiparity reduces the risk of PE, and among nonpregnant women, multiparity has a protective effect on blood pressure in women below 40 years of age, an effect that is related to the number of births.…”
Section: Discussionmentioning
confidence: 99%
“…In general, multiparity reduces the risk of PE, and among nonpregnant women, multiparity has a protective effect on blood pressure in women below 40 years of age, an effect that is related to the number of births. 30 A change in paternity is probably the best known risk factor for PE in multiparous women, with OR of 1.30-1.56 for PE, depending on the diagnostic criteria, and an OR of 1.99 for the combined group of pregnancy-related hypertensive disorders regardless of diagnostic criteria. 31 However, this effect is influenced by the history of PE with the previous partner, being increased among women without, and decreased in women with, PE in the preceding pregnancy.…”
Section: Non-immune Immune Non-immune Immunementioning
confidence: 99%